New mutants classic, volume 2 ebook - Claremont, Chris (New Mutants (1983), 2014)
Collects New Mutants (1983) #8-17. Nova Roma, a city on the move - back several thousand years! In their earliest adventure abroad, the New Mutants discover a long-forgotten colony of the Roman Empire and an enemy they won't soon forget: Selene the Black Queen! Then, Magma and Magik join the team just in time for war with the White Queen! Featuring the future Warpath and the original Hellions, harbingers of horror and heroism for years to come!